Seinfeld and philosophy : a book about everything and nothing / edited by William Irwin. - Irwin, William, 1970- (Open Court, 2000)
An introduction to philosophy through the lens of "Seinfeld" asks, "Is it rational for George to do the opposite?" and "Is there really anything wrong with that?" and other important topics.
Keywords: Philosophy -- Miscellanea.; Seinfeld (Television program) -- Miscellanea.; Seinfeld (Fernsehsendung)